Recovery from sport-induced muscle damage in relation to match-intervals in major events - Nosaka, Kazunori; Chen, Trevor C. (Frontiers in Sports and Active Living, 2024)
Muscle damage could affect the next match performance in sports when the time to recover from a previous match is shorter. We examined the interval between matches in nine team sports (e.g., soccer, rugby, field hockey, basketball, volleyball, baseball) and two racket sports (badminton, tennis) in World Cups held in 2022-2023, 2020 Tokyo Olympic Games and Gland Slam in 2023. We then performed narrative review using three electronic databases (PubMed, Scopus, Google Scholar) to get information about muscle damage and recovery in the 11 sports, and discussed whether the intervals in the events would be enough for athletes. We found that the match intervals varied among sports and events ranging from 0 to 17 days. The interval was the shortest for softball (0–2 days) and the longest (5–17 days) for rugby. Regarding muscle damage, changes in muscle function and/or performance measures after a match were not reported for cricket, volleyball and softball, but some information was available for other sports, although the studies did not necessarily use athletes who participated in the major events. It was found that recovery was longer for soccer and rugby than other sports. Importantly, the match-intervals in the events did not appear to accommodate the recovery time required from the previous match in many sports. This could increase a risk of injury and affect players’ conditions and health. Changing the match-intervals may be difficult, since it affects the budget of sporting events, but an adequate interval between matches should be considered for each sport from the player’s and coach's point of view.